The where and how of faults, fluids and permeability – insights from fault stepovers, scaling properties and gold mineralisation. Issue 1 (24th September 2014) - Micklethwaite, S.; Ford, A.; Witt, W.; Sheldon, H. A.
Abstract Fault stepovers are features where the main trace of a fault steps from one segment to the next in either an underlapping or overlapping manner. Stepovers exert a critical influence on crustal permeability and are known to control phenomena such as the migration of hydrocarbons and the location of geothermal fields. In the Kalgoorlie‐Ora Banda greenstone district, Western Australia, we demonstrate a spatial association between stepovers and gold deposits. It is shown that although underlapping stepover geometries are typically rare in fault systems, they are anomalously associated with gold deposits. Further, the along‐strike and across‐strike dimensions of both underlapping and overlapping fault stepovers fit, to a first‐order approximation, the same self‐similar trend. Boundary element modelling of Coulomb failure stress changes is used to explain these observations in terms of damage generated by rupture events on the bounding fault segments and associated aftershock sequences. Our models indicate that a larger region of damage and permeability enhancement is created around underlapping stepovers than around overlapping stepovers. By taking into account both the enhancement and decay of permeability during the seismic cycle, it is estimated that a 5 Moz goldfield could feasibly form in 1–16 earthquake‐aftershock sequences, potentially representing durations of just 10–8000 years. The existence of supergiant gold deposits is evidence that crustal permeability attains transiently high values on the order of 10−12 m2. It should be expected that transient and time‐integrated permeability values have a distinct three‐dimensional structure in continental crust due to stepover‐related channels.